The Perisphere, New York World's Fair (Curt Teich & Co.)
The Perisphere rises over the edge of a 16-foot serpentine hedge and huge flower-bed at the World's Fair of 1940 in New York like a one-ringed Saturn - the ring in this case being the spiral ramp down which people are seen making their exit from the "Democracity" spectacle which is staged inside the great globe.